Bridging Tasawwuf and Maqāṣid al-Sharīʿah: An Ethical Foundation for Muslim Social Welfare in Contemporary Societies - Jimmy Malintang; Jamaluddin Majid (International Forum of Researchers and Lecturers, 2025)
This study explores the integration of Tasawwuf (Islamic mysticism) with Maqāṣid al-Sharīʿah (objectives of Islamic law) to propose a more ethical and effective social welfare framework. The research emphasizes the importance of combining the spiritual dimensions of Tasawwuf, such as Ihsan (excellence) and ʿAdl (justice), with the legal and ethical framework of Maqāṣid al-Sharīʿah, which seeks to preserve essential human interests such as religion, life, intellect, progeny, and wealth. This integrated approach is positioned as a comprehensive model for social welfare that addresses not only material needs but also promotes spiritual growth and ethical conduct. By blending these two frameworks, the study proposes a holistic view of social welfare that fosters empathy, justice, and social care. The findings highlight that Tasawwuf contributes to the ethical application of Maqāṣid al-Sharīʿah, enhancing social responsibility and promoting greater community cohesion and solidarity. The study also discusses the practical implications of this integration in contemporary Muslim societies, including its potential to reshape existing welfare programs. Recommendations for future research and policy development emphasize the need for further exploration of this integrated approach in Islamic finance, Takaful, and Zakat, as well as the creation of frameworks that balance legal compliance with ethical and spiritual principles. The results suggest that incorporating Tasawwuf alongside Maqāṣid al-Sharīʿah can significantly improve the ethical foundation of social welfare programs, fostering a more just and compassionate society.